Interpretation of tree-ring chronologies - Esper, Jan; Gärtner, Holger (ERDKUNDE, 2001)
To interpret published tree-ring chronologies and to use these results for geographic studies, knowledge about essential aspects of chronology building is necessary. For example, most chronologies display climatic variation in the wavelengths of years to decades. Trends on longer time-scales, like century-scale variation, are generally more difficult to emphasize and often missing in tree-ring chronologies. Here we aim to explain such facts and to generate a basic understanding of current dendrochronological techniques, thus allowing successful interpretation of tree-ring chronologies and the strength of this method to be understood.